Metformin: A Narrative Review of Its Potential Benefits for Cardiovascular Disease, Cancer and Dementia - Wiebe M. C. Top; Adriaan Kooy; Coen D. A. Stehouwer (MDPI AG, 2022)
The biguanide metformin has been used as first-line therapy in type 2 diabetes mellitus (T2DM) treatment for several decades. In addition to its glucose-lowering properties and its prevention of weight gain, the landmark UK Prospective Diabetes Study (UKPDS) demonstrated cardioprotective properties in obese T2DM patients. Coupled with a favorable side effect profile and low cost, metformin has become the cornerstone in the treatment of T2DM worldwide. In addition, metformin is increasingly being investigated for its potential anticancer and neuroprotective properties both in T2DM patients and non-diabetic individuals. In the meantime, new drugs with powerful cardioprotective properties have been introduced and compete with metformin for its place in the treatment of T2DM. In this review we will discuss actual insights in the various working mechanisms of metformin and the evidence for its beneficial effects on (the prevention of) cardiovascular disease, cancer and dementia. In addition to observational evidence, emphasis is placed on randomized trials and recent meta-analyses to obtain an up-to-date overview of the use of metformin in clinical practice.